A model predictive control strategy for enhancing fault ride through in PMSG wind turbines using SMES and improved GSC control - Abdelkader, Sobhy M.; Morgan, Ernest F.; Megahed, Tamer F.; Rohouma, Wesam; Abdel-Rahim, Omar (Frontiers in Energy Research, 2023)
Wind energy has emerged as a prominent player in the realm of renewable energy sources, both in terms of capacity and technological adaptability. Among the various renewable energy technologies, wind turbine generators (WTGs) stand out as the most widely employed. Recently, gearless permanent magnet synchronous generators (PMSGs) have gained traction in the wind energy sector due to their appealing features, such as reduced maintenance costs and the elimination of gearboxes. Nevertheless, challenges remain, particularly concerning the grid-friendly integration of wind turbines, specifically with regard to high voltage ride-through (HVRT) and low voltage ride-through (LVRT) improvements. These challenges pose a threat to grid stability, impede WTG performance, and may lead to significant damage to wind turbines. To address these concerns, this research proposes an integrated strategy that combines a model predictive controlled (MPC) superconducting magnetic energy storage (SMES) device with a modified WTG grid-side converter control. By coupling SMES devices to the dc-link of PMSG WTGs, the proposed approach aims to achieve an overvoltage suppression effect during grid disturbances and provide support for grid reactive power. Through various test scenarios, the feasibility and practicality of this suggested technique are demonstrated